The life and adventures of Robinson Crusoe - Defoe, Daniel, 1661?-1731.; Duvoisin, Roger, 1900- (Cleveland : World Publishing Company, 1946)
The diary of an Englishman shipwrecked for almost thirty years on a small isolated island where, using wit and industry, he manages to build life anew.
Map on lining papers.
1.
Keywords: English fiction